pedro estava resolvendo a seguinte expressão 14+(-44+30).2+(2.4+3). qual o resultado encontrado por pedro.
Soluções para a tarefa
Respondido por
1
Resposta:
23
Explicação passo-a-passo:
(-44+30).2+(2.4+3)
(+6).2+(2.4+3)
(+6).2+(8+3)
12+(8+3)
12+11
23
Respondido por
0
Resposta:
Explicação passo-a-passo:
14+(-44+30).2+(2.4+3) =
14 + (-14).2 + (8+3)=
14 + (-28) + 11 =
14 - 28 + 11 =
-3
Perguntas interessantes
Matemática,
10 meses atrás
Pedagogia,
10 meses atrás
Português,
10 meses atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás